EVALUATION AND IMPROVEMENT OF THE LEVEL OF SERVICE OF MULTI-LANE HIGHWAYS IN JORDAN (Advances in Civil and Architectural Engineering, 2021)
The study aims to analyze, evaluate, and improve the level of service (LOC) of multi-lane highways in Jordan. The Alhizam multi-lane rural highway in Jordan was selected as a case study as it is considered a major arterial highway with high traffic volume. The traffic data was collected from governmental records of different departments in the Ministry of Public Work and Housing during the summer period of 2015. HCS-2000 and HCS-2010 software were used to evaluate the LOC for the existing, short-term (year 2020), and medium-term (year 2025) conditions. Some of the highway’s segments operate at LOS-E or LOS-F for short-term and medium-term conditions. For these segments, the short-term or medium-term conditions were improved through the modification of geometric and traffic conditions so that the segments operate at LOS-C or LOS-D. Management flow diagrams were prepared to provide decision-makers with a useful tool for the planning of rural multi-lane highways in Jordan.